Targets in International Climate Policyː (Mis)understanding Two Degrees? - Felix Otto; Hermann Held (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2022)
This article investigates the genesis and role of the 2° target in international climate policy. We identify a dual role played by temperature targets: (i) a social planner's option of decision making under uncertainty that draws on the precautionary principle, and (ii) a policy instrument to help the social planners' position become reality. Accordingly, the recent debate over the 2° target as found in the literature is actually a mutual misunderstanding: while the opponents mainly focus on the policy instrument function, the proponents focus on the social planner solution. By publishing this article, we hope to contribute to a more "targeted" dialogue in the future. In order to achieve this, the article analyses the concept of targets and argues that an environmental target always consists of three elements, namely (a) science or system knowledge, (b) norms and values, and (c) an operational perspective. Further, it investigates how targets were defined in international climate policy and how they have evolved over time. In 1997, emission targets were defined in the Kyoto Protocol. In 2015, the 2° target, based on the precautionary principle, was implemented in the Paris Agreement. Learning from the case of sulphur dioxide policy, another example of environmental policy, when considering how the 2° target could be made more effective, one might be tempted to underpin it with impact-related findings that are as concrete as possible - or to replace it with corresponding impact-based targets. However, many actors might contend that the totality of global warming impacts is still hard to judge. Accordingly, the 2° target should also serve as an expression of precaution, as an interim solution of sorts, until we acquired a more comprehensive grasp of climate impacts.
Keywords: 330; target; climate policy; Precautionary Principle; international environmental policy